DETERMINAN KEJADIAN OBESITAS PADA MASYARAKAT DEWASA DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KOTA PEKANBARU: DETERMINAN KEJADIAN OBESITAS PADA MASYARAKAT DEWASA DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA PEKANBARU - Agus Alamsyah; M.Kamali Zaman; Winda Septiani (STIKes Hang Tuah Pekanbaru, 2019)
Obese is a overweight as a result of plutonium body fat excessive. Based on the data from health department the city of pekanbaru 2016 the proportion of the incident obesity was highest for puskesmas simpang three of which was 2.1 % per 19.029 population. Based on preliminary survey, than 20 respondents there were as many as five people ( 25 % ) suffering from obesity. Obesity have an impact on the emergence of various degenerative diseases among others, metabolic syndrome atherosclerosis, of cardiovascular diseases, diabetes, gallstones, disturbance of function pulmonic, hypertension and dislipidemia. Research objectives know determinan scene obesity in community in the work area of puskesmas simpang 3 the city of pekanbaru 2017. The research was quantitative analytic with a kind of design study cross section analitik. Variabel dependent obesity and independent variable was education, knowledge, sex, offspring, physical activity and the habit of eating. The study was done in the work area of puskesmas simpang 3 the city of pekanbaru, data collection was held in december 2017 - january 2018. Population to research it was a whole people living and settled in the work area of puskesmas simpang 3 the city of pekanbaru 2018 as many as 19.029 lives and sample were 155 responden. teknik the sample collection of sampling quota. Data analyswas univariat, bivariat and multivariate. The results of the study showed that well educated low (SMP), the offspring of obesity and the habit of eating little influence to events obesity. It was suggested that puskesmas simpang 3 the city of pekanbaru harder socialize a healthy lifestyle like how diet good to avoid from obesity especially the targets to the education low and have the acts of offspring obesity.